Comparison of the AmpFire® Multiplex HPV Assay to the Xpert® HPV Assay for detection of human papillomavirus and cervical disease in women with human immunodeficiency virus: a pragmatic performance evaluation - Sikhulile Moyo; Doreen Ramogola-Masire; Natasha O. Moraka; Leabaneng Tawe; Farzad Noubary; Kesego Motsumi; Godiraone Manowe; Boitumelo Zuze; Botshelo Radibe; Faith T. T. Hungwe; Terence Mohammed; Comfort Maphorisa; et al. (Infectious Agents and Cancer, 2023)
Abstract Background Low- and middle-income countries (LMICs) account for nearly 85% of the global cervical cancer burden, yet have the least access to high-performance screening. International guidelines recommend human papillomavirus testing (HPV) as primary screening, yet implementation is inhibited by the cost of HPV testing. Atila AmpFire® HPV Assay (AmpFire) is both affordable and easy to use, and offers individual genotyping. The objective of this study was to compare the performance of the AmpFire HPV assay to the Xpert® HPV assay in detection of both HPV and clinically significant cervical disease. Methods We utilized stored cervical specimens from a prospective cohort study of women living with human immunodeficiency virus (HIV) in Botswana conducted from May to July 2018. Positive and negative percent agreement was calculated for the AmpFire and Xpert assays, as was detection of high-grade cervical dysplasia. Results 63 stored cervical specimens had detectable DNA after thawing and were included in the analysis. The positive percent agreement was 91.2% (95%CI 76.3–98.1) and negative percent agreement was 79.3% (95% CI 60.3–92.0). Six cases positive by AmpFire but negative by Xpert were HPV genotypes 35, 52 (n = 2), 58, 68, and co-infection with HPV 45 and 68. Both Xpert and AmpFire assays detected HPV in all 10 samples of women who had high-grade cervical dysplasia. Conclusions The AmpFire HPV assay demonstrated excellent analytic performance in both detection of HPV and clinically significant cervical disease. AmpFire HPV is a promising option to increase access to affordable, type-specific HPV screening for cervical cancer in LMICs.